(untitled) (Medico Legal Update, 2020)
Background: Patients in cardiac rehabilitation are typically advised to complete a period of maintenance phase. The purpose of this study was to determine if there was any difference in effect of aerobic training on selected cardiopulmonary parameters in myocardial infarction patients with stroke. Methodology: Forty patients of both sexes with age 40-50 years with chronic myocardial infarction patients with stroke after 6 months participated in the study. Patient’s were assigned for 4 weeks into two groups: group (A) received aerobic training and traditional physical therapy program and group (B) which received traditional physical therapy program. Patients were assessed pre and post treatment using through Stress exercise test unit (Modified Bruce protocol) and modified ashwarth scale. Results: This study revealed that there is significantly improved in resting heart rate (10.10%), maximum heart rate (4.67%), METs (64.95%), maximum systolic blood pressure (4.45%), maximum diastolic blood pressure (9.45%) and VO2 max (35.36%) variables in group (A) treated by aerobic training than those of traditional physical therapy program only. Conclusion: Aerobic training was a valuable method for management myocardial infarction patients with stroke.